The Impact of ICT on Career Counseling Services: A case Study of Nigerian Secondary Schools - Obi M. C.; Oye N. D.; Mohd T. N.; Bernice A. (Institute of Advanced Engineering and Science, 2012)
Information and communication technologies (ICT) will need to be fully integrated into the delivery of careers services as the world is now in the global era. Such integration would not only have the potential to achieve more but would also increase the flexibility of services and enhance their quality. Career choice is an important decision a person needs to make in his life time. Unfortunately, many young people find it uneasy to make appropriate career choice. The paper focused on the usage of career counseling services in selected public secondary schools in Nigeria. It sought to find out how students and teachers utilize career counseling services, students’ expectations in career counseling services and how school principals support career counseling services. Simple random sampling was used to select 380 from 34 public secondary schools from the sample population. Four-point Likert scale questionnaires were used to obtain data for the study. The findings revealed that the students use career counseling services to take career decision and aspiration, gather career information and select and take subjects that match their career interest. Secondary school teachers use career counseling services to guide students to make appropriate subject choice that match their career interest and help them with their career challenges and plans. This paper recommends that career counselors should integrate use of ICT, through the use of chat rooms, email and social networking. In other words several choice of career could be show to the students on DVD and CD Video. They should also be exposed to TV and radio Chat on Career choice.DOI: http://dx.doi.org/10.11591/ijere.v1i1.709